Experimentando Materia Tintóreas Entre el Nuevo Mundo y Europa: Narrativas y Muestras en los Archivos de la Monarquía Hispanica (Siglo XVI) (Glocalism: Journal of Culture, Politics and Innovation, 2021)
This article analyzes the emergence of applied sciences in the field of two American dyeing materials – the woad called ek and the indigo – in the Spanish Empire. It highlights how the circulation of written documents and displays of materials situated local knowledge and experiences in a global framework in which a wide range of actors was engaged from Mexico City, Campeche, Mérida (Yucatan), Seville, Madrid or Milan. We will also show that the Spaniards tended to obscure the Native origin of their so-called “inventions” in order to secure privileges in the production and commercialization of these materials. On the other hand, we examine the Council of the Indies efforts to stimulate the production of knowledge, to organize and intertwine information, and to promote the imperial economic interests. The article thus demonstrates how the analysis of the Spanish Monarchy’s archivistic practices is key to fully understanding the emergence of the Renaissance scientific culture.
Keywords: archive; scientific culture; dyeing materials; Native people; Spanish Monarchy